First record of Paramyrothecium roridum as a causative agent of melon stem blight in Iraq - Eman Jabbar Mohammed; Alaa O. Manea1 (University of Thi-Qar Journal of agricultural research, 2024)
The study was conducted in the Plant Pathology Laboratory of the Department of Plant Protection, College of Agriculture, University of Basrah, during the period 2023-2024. The study aimed to isolate and identify the pathogen Paramyrothecium roridum associated with melon stem blight disease morphologically and molecularly, evaluate its pathogenicity, and test the effect of chitosan on fungal growth in vitro conditions and the effect of the Bioagent Trichoderma viride on the pathogenic fungus. The results of the morphological diagnosis showed that the fungus consists of fungal colonies in the form of concentric circles and an identification color. As the colony ages, the color becomes darker and the nature of the fungus growth is slow. It takes 10 days for the fungus to fill the entire plate. The results of the pathogenicity showed that the tested isolate caused the death of melon seedlings grown in pots. The germination rate and seedling death reached 56.66 and 36.33%, respectively, compared to the control treatment, which had a germination rate of 80.00 and seedling death of 4.00. The results showed The inhibition of chitosan at concentrations of 2%, 3% and 5% g/L the concentration of 5% excelled by achieving a high inhibition rate, as the inhibition rate of fungal growth reached 100.00%, while the results of the antagonism with the bio fungus T. viride in the dual cultivation experiment were that the bio fungus T. viride has a high antagonistic ability in the PDA culture medium against the pathogenic fungus, as the antagonism degree reached 1.